CHILDREN EMOTIONS IN BIG HERO 6 MOVIE - NASRUM MARJUNI (JURNAL LINER (Language Intelligence and Educational Research), 2018)
This research was about children emotions which aimed to describe children emotion portrayal of the main character in Big Hero 6 Movie. It applied descriptive qualitative method in revealing the data. In collecting the data, the researchers used note taking as instrument to get valid data. The researchers found some children emotions portrayal such as: Emotions of joy, anger, fear, grief, curiosity and affection. Keywords: Children, Emotion, Big Hero 6, Movie